Anaplasic large cell lymphoma ALK plus Anatomo pathological characterization of three pediatric cases - Cao, Gabriel Fernando (2023)
The anaplastic large cell lymphoma ALK+ (ALCL ALK+) is a rare malignancy in childhood, which normally occurs in advanced clinical stages. The common histological subtype is composed by large cells with cytomorphology and immunohistochemistry feature of CD30 and T markers expression. The neoplasia presents a translocation t (2; 3) (p23; q35) related to up- regulated of kinase associated with anaplastic cells (ALK), whose overexpression is detectable by immunohistochemical techniques (ALK-1). The presence of lymphadenopathies and prolonged fever can simulate an infectious process. The presence of B symptoms, extranodal, mediastinal, visceral and cutaneous involvement, significantly reduce the prognosis of the patient. Medullary infiltration at the time of the diagnosis, together with the histological subtypes of small cells and lymphohistiocytic neoplasm, favouring frequent relapses. Treatment is based on different regimens and combine cytarabine, methotrexate, doxorubicin, prednisolone, vincristine, and 6-mercaptopurine. Other therapies include the use of an anti-CD30 antibody and an ALK enzyme inhibitor drug.